Korea and Germany as endpoints of the new silk road: Opportunities for cooperation - Hans-Ulrich Seidt (OrdnungsPolitisches Portal (OPO), 2021)
The transforming world of the 21st century has entered a new era. It is characterized by geopolitical conflicts, controversial grand strategies and disruptive events. Over the next years, the Sino-American competition will throw a dark shadow over international relations, global mega-infrastructure projects and the world's maritime trade routes. The current situation highlights the need for a renewed multilateralism and closer cooperation between like-minded countries like the Republic of Korea and Germany.
Keywords: 330; German-Korean cooperation; China's grand strategy; U.S. threat assessment; great power competition; new silk road